Percutaneous suction and irrigation for the treatment of recalcitrant pyogenic spondylodiscitis - William Griffith-Jones (Journal of Orthopaedics and Traumatology, 2018)
Abstract Background The primary management of pyogenic spondylodiscitis is conservative. Once the causative organism has been identified, by blood culture or biopsy, administration of appropriate intravenous antibiotics is started. Occasionally patients do not respond to antibiotics and surgical irrigation and debridement is needed. The treatment of these cases is challenging and controversial. Furthermore, many affected patients have significant comorbidities often precluding more extensive surgical intervention. The aim of this study is to describe early results of a novel, minimally invasive percutaneous technique for disc irrigation and debridement in pyogenic spondylodiscitis. Materials and methods A series of 10 consecutive patients diagnosed with pyogenic spondylodiscitis received percutaneous disc irrigation and debridement. The procedure was performed by inserting two Jamshidi needles percutaneously into the disc space. Indications for surgery were poor response to antibiotic therapy (8 patients) and the need for more extensive biopsy (2 patients). Pre- and postoperative white blood cell count (WBC), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), Oswestry disability index (ODI), and visual analogue score (VAS) for back pain were collected. Minimum follow-up was 18 months, with regular interval assessments. Results There were 7 males and 3 females with a mean age of 67 years. The mean WBC before surgery was 14.63 × 109/L (10.9–26.4) and dropped to 7.48 × 109/L (5.6–9.8) after surgery. The mean preoperative CRP was 188 mg/L (111–250) and decreased to 13.83 mg/L (5–21) after surgery. Similar improvements were seen with ESR. All patients reported significant improvements in ODI and VAS scores after surgery. The average hospital stay after surgery was 8.17 days. All patients had resolution of the infection, and there were no complications associated with the procedure. Conclusions Our study confirms the feasibility and safety of our percutaneous technique for irrigation and debridement of pyogenic spondylodiscitis. Percutaneous irrigation and suction offers a truly minimally invasive option for managing recalcitrant spondylodiscitis or for diagnostic purposes. The approach used is very similar to discography and can be easily adapted to different hospital settings. Level of Evidence Level III